2019
DOI: 10.4322/acr.2018.081
|View full text |Cite
|
Sign up to set email alerts
|

Infantile systemic juvenile xanthogranuloma case with massive liver infiltration

Abstract: Infantile systemic juvenile xanthogranuloma (ISJXG) is an uncommon form of juvenile xanthogranuloma, a non-Langerhans cell proliferation of infancy and early childhood. In a small percentage of patients, the visceral involvement—most commonly to the central nervous system, liver, spleen, or lungs—may be associated with severe morbidity, and eventually fatal outcome. Here we describe the clinical and pathological findings of a 28-day-old girl with ISJXG who died with respiratory distress syndrome. She had few c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…This current finding may be similar to a JXG autopsy finding in which histiocytes in the portal tract spilled over into the adjacent lobule. 16 In DWI in the current case, the nodule located on the right liver subcapsular region showed slightly restricted diffusion and curvilinear high intensity was present along the periportal vein. To the best of our knowledge, the MRI appearance of lesions in the liver has not been described previously.…”
Section: Discussionmentioning
confidence: 48%
“…This current finding may be similar to a JXG autopsy finding in which histiocytes in the portal tract spilled over into the adjacent lobule. 16 In DWI in the current case, the nodule located on the right liver subcapsular region showed slightly restricted diffusion and curvilinear high intensity was present along the periportal vein. To the best of our knowledge, the MRI appearance of lesions in the liver has not been described previously.…”
Section: Discussionmentioning
confidence: 48%
“…JXG typically presents yellow to pink-brown papules and nodules; 16 of the 32 cases presented a typical color (such as yellow and erythematous) [ 1 , 5 , 10 12 , 14 22 ], with three of the 16 cases subsequently changing to a typical color [ 5 , 12 , 22 ]. Eight cases had atypical skin lesions; one case had purpura (as in our case) [ 23 ], and the others had bluish nodules, ecchymoses, petechiae, blueberry muffin rash, and a mass [ 4 , 6 , 13 , 23 27 ]. Six cases had unclear in the details [ 2 , 7 , 28 30 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The child underwent surgical excision of the cardiac JXG and chemotherapy, and is now 6 years of age and healthy. Mortality is extremely rare but has been reported in infants with central nervous system or massive hepatic involvement 17,18 …”
Section: Discussionmentioning
confidence: 99%
“…Mortality is extremely rare but has been reported in infants with central nervous system or massive hepatic involvement. 17,18 An important but controversial association of multiple JXGs is JMML, especially in the presence of concomitant NF-1. 19 20 Zvulunov et al reported a 20-32-fold higher risk of developing JMML in patients with NF-1 and concomitant multiple JXG compared to NF-1 alone.…”
Section: Jxg Is the Most Common Cutaneous Form Of Non-langerhans Cell...mentioning
confidence: 99%